Manajemen Industri Olaharaga Arung Jeram di Rainbow Rafting Kabupaten Pemalang - Prakoso, Agung Ifnu (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is to describe the management include planning, organizing, directing, and monitoring the management of the sports industry in the district Rafting Rainbow Pemalang 2014. This study used a qualitative research approach deskripstif. Research sites in Rainbow Rafting Pemalang districtThe results of this study were 1) the planning process undertaken by management Rainbow Rafting has been running in accordance with management functions, 2) Management of its organization already implemented the basics of a good organization, 3) alignment process is conducted by a general manager has been implemented with good , and 4) Monitoring is carried out by the management Rainbow Rafting has been running according to function. Conclusion that the process of planning, organizing, directing, and management oversight Rainbow Rafting Pemalang district in 2014 has been good, and the management has carried out the functions and processes as appropriate.